2008
DOI: 10.1371/journal.ppat.0040037
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Biosynthesis Is Critical for Growth of Bacteria in Human Blood

Abstract: Proliferation of bacterial pathogens in blood represents one of the most dangerous stages of infection. Growth in blood serum depends on the ability of a pathogen to adjust metabolism to match the availability of nutrients. Although certain nutrients are scarce in blood and need to be de novo synthesized by proliferating bacteria, it is unclear which metabolic pathways are critical for bacterial growth in blood. In this study, we identified metabolic functions that are essential specifically for bacterial grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
206
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(228 citation statements)
references
References 53 publications
(61 reference statements)
21
206
1
Order By: Relevance
“…The Keio Collection has been used by many groups to observe the effects of gene deletions under specific conditions of interest. These studies have included the determination of mutations affecting antibiotic hypersensitivity (2,3), swarming motility (4), biofilm formation (5), growth in human blood (6), recipient ability in plasmid conjugation (7), cysteine tolerance and production (8), colicin import and cytotoxicity (9), de-ethylation of 7-ethoxycoumarin (10), and glycogen metabolism (11). In most of these studies, the sets of relevant gene deletions show enrichment for specific cellular functions linked to the conditions of the screen.…”
mentioning
confidence: 99%
“…The Keio Collection has been used by many groups to observe the effects of gene deletions under specific conditions of interest. These studies have included the determination of mutations affecting antibiotic hypersensitivity (2,3), swarming motility (4), biofilm formation (5), growth in human blood (6), recipient ability in plasmid conjugation (7), cysteine tolerance and production (8), colicin import and cytotoxicity (9), de-ethylation of 7-ethoxycoumarin (10), and glycogen metabolism (11). In most of these studies, the sets of relevant gene deletions show enrichment for specific cellular functions linked to the conditions of the screen.…”
mentioning
confidence: 99%
“…It is also interesting that the S. sanguinis purB mutant is attenuated in both biofilm formation and virulence for endocarditis whereas the purL mutant exhibits only biofilm reduction. Both the purB gene and the purL gene have been shown to be important for virulence in studies performed with S. pneumoniae (38) and with Bacillus anthracis (65). Given these results and the overall similarity of the S. pneumoniae and S. sanguinis purine pathways (P. Xu, unpublished observations), it is more surprising that purL is not required for virulence in S. sanguinis than that purB is.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, this rate-limiting DNA biosynthesis enzyme has a 56601-specific missense mutation causing an A703T substitution within a barrel domain. It was previously reported that, compared with other metabolic pathways, inactivation of purine/pyrimidine pathway genes in Escherichia coli and some other bacteria was the key factor for limiting their growth in human serum [25]. Therefore, these variations are likely, to a certain extent, to contribute to the avirulence property of strain IPAV.…”
Section: Protein Quantification and Comparative Proteomic Analysis Ofmentioning
confidence: 99%